Technical women on corporate boards. - Bretz, E.A.
In the rarefied boardroom atmosphere, women still maintain only a small presence. To get a first-hand view of life on a board from a female perspective, this article details four women scientists and engineers who are corporate directors. That these women came-from diverse technical backgrounds and arrived at their board memberships by a variety of career paths attests to the fact that there is no one road to the boardroom. Instead, it appears that hard work, a solid professional reputation, the pursuit of career, community and personal activities outside of one's narrow job description, and, above all, assiduous attention to maintaining good professional relationships are key ingredients for a boardroom invitation
Keywords: Career; Career paths; Corporate boards; Corporate directors; Engineering managers; Personal activities; Professional relationships; Professional reputation; Women engineers; Women scientists